Peçonha de Bothrops alternatus: avaliação in vitro da atividade antiviral contra a infecção pelo vírus da dengue e a influência de uma toxina isolada na secreção de citocinas - Dias, Edigar Henrique Vaz (2015)
The snake venom has a promising future for medicine because their components have various physiological and pharmacological effects when interacting with molecules of cells. These components can be used as therapeutic agents, diagnostic markers for various diseases and research tools for deciphering physiological and pathological processes in humans. Our study aimed to isolate a phospholipase A2 from the venom of Bothrops alternatus and characterize their influence on the release of pro and anti-inflammatory cytokines and analyze its action on the antiviral effect against dengue virus serotype 2. The toxin PLA2 Ba3dP7 had a molecular weight of approximately 17 kDa and has the ability to stimulate the production of IL-10, IL-12 and TNF-α, however, the expression of the latter two was statistically significant compared with the production of IL- 10, suggesting a proinflammatory profile of this toxin (p <0.05). The results also showed that the toxin stimulated nitric oxide production, which enhances the proinflammatory role of PLA2 Ba3dP7, thus this toxin may be an important protein related to inflammatory processes generated by poisoning by snakes of the species B. alternatus. It was observed that the crude venom decreased cytotoxicity generated by DENV 2 after pre-treatment of C6/36 cells with the same, possibly featuring its protective role against viral infection. Furthermore, the crude venom showed virucidal activity (p <0.05). Importantly, more studies are needed to determine which (es) component (s) present in the venom is (are) responsible (s) for the protection activity and for virucidal action.